(3Yjf GdYHQI aj ZHf GdYJQIs - (3CMeO Hf ehSi Hf LYaQ Hf eMeO GHf WGhhS GdYdhqj GdMSfj GdMdj, LeGd GdOjf, J (B673 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO aEf ef Sda GdCaGVd LejY eG Gfab dg s
(3BNQgG (B:s
(3HhUGd Rjf GdfLGI Je cJGH Yjf GdYHQI s
(3cJHg Ydi fSNI SbjeI cKjQI GdZdW hGdJMQjas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B132s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis